2022
DOI: 10.3390/genes13061068
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of the WRKY Gene Family in Malus domestica and the Role of MdWRKY70L in Response to Drought and Salt Stresses

Abstract: The WRKY transcription factors are unique regulatory proteins in plants, which are important in the stress responses of plants. In this study, 113 WRKY genes were identified from the apple genome GDDH13 and a comprehensive analysis was performed, including chromosome mapping, and phylogenetic, motif and collinearity analysis. MdWRKYs are expressed in different tissues, such as seeds, flowers, stems and leaves. We analyzed seven WRKY proteins in different groups and found that all of them were localized in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 59 publications
(77 reference statements)
1
10
0
Order By: Relevance
“…The number of AP2/ERF genes reported in the pan-genome ( 145) is higher than earlier reports (132) by Dossa et al, 2016 in sesame with wide difference in classification. In the WRKY family, we detected 89 genes in the pan-genome, much lesser than reported in sorghum (94), rice (104), Arabidopsis (74), apple (113), soybean (174) and sunflower (119) (Yang et al, 2017;Baillo et al, 2020;Liu et al, 2020;Abdullah-Zawawi et al, 2021;Qin et al, 2022). Like other crops, in…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The number of AP2/ERF genes reported in the pan-genome ( 145) is higher than earlier reports (132) by Dossa et al, 2016 in sesame with wide difference in classification. In the WRKY family, we detected 89 genes in the pan-genome, much lesser than reported in sorghum (94), rice (104), Arabidopsis (74), apple (113), soybean (174) and sunflower (119) (Yang et al, 2017;Baillo et al, 2020;Liu et al, 2020;Abdullah-Zawawi et al, 2021;Qin et al, 2022). Like other crops, in…”
Section: Discussionmentioning
confidence: 71%
“…WRKY TF family is the seventh largest and contains the signature domain of 60-70 amino acids representing WRKYGQK/WRKYGKK at the Nterminus and a Zn-finger domain at the C-terminus (Yang et al, 2017). Genome-wide characterization of WRKY genes has been reported in soybean (Yang et al, 2017) against cyst nematode, sorghum (Baillo et al, 2020) against multiple stress responses, the biotic and abiotic stress response in sunflower (Liu et al, 2020), the abiotic stress response in apple (Qin et al, 2022) and sesame (Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the existence of WRKY subfamilyⅠgene binding dual W-box elements (Liu et al 2021). Based on this, we performed a screening assay for WRKY subfamilyⅠ gene-binding WRKY40 DWE elements using yeast one-hybrid (Qin et al 2022). The results showed that WRKY1 binds to the DEW element of WRKY40, and that mutation of any of the W-boxes of the DWE element inhibits the binding of WRKY1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…WRKY genes are a vast family of TFs that are present in almost all plant species and serve key roles in a variety of physiological functions ( Rinerson et al, 2015 ; Li W. et al, 2020 ; Wani et al, 2021 ). Numerous plant species have had their WRKY TFs identified at the entire genome level ( Guo et al, 2014 ; He et al, 2016 ; Kumar et al, 2016 ; Wang et al, 2019 ; Chen et al, 2020b ; Qin et al, 2022 ). In this research, we reported a genome-wide analysis of the WRKY family in azalea and 57 RsWRKY genes was identified.…”
Section: Discussionmentioning
confidence: 99%
“…The WRKY proteins of following species were retrieved from prior studies: Arabidopsis thaliana ( Eulgem et al, 2000 ), Brassica napus ( He et al, 2016 ), Malus domestica ( Qin et al, 2022 ), Camellia sinensis ( Wang et al, 2019 ), Cucumis sativus ( Chen et al, 2020b ), Physcomitrella patens ( Rensing et al, 2008 ), Theobroma cacao ( Silva Monteiro de Almeida et al, 2017 ), Medicago truncatula ( Kumar et al, 2016 ), Cyanidioschyzon merolae ( Dou et al, 2014 ), rice ( Oryza sativa ) ( Ramamoorthy et al, 2008 ), Ginkgo biloba ( Cheng et al, 2019 ), Chlamydomonas reinhardtii ( Rinerson et al, 2015 ), Vitis vinifera ( Guo et al, 2014 ), Solanum melongena ( Yang Y. et al, 2020 ), Azolla filiculoides ( Zhao et al, 2021 ), Salvinia cucullate ( Zhao et al, 2021 ), Selaginella moellendorffii ( Rinerson et al, 2015 ), Moringa oleifera ( Zhang et al, 2019 ), Solanum lycopersicum ( Huang et al, 2012 ), Sorghum bicolor ( Baillo et al, 2020 ) and Populus trichocarpa ( Jiang et al, 2014 ). The evolutionary relationships of these species were determined according to the PGDD database ( Lee et al, 2013 ) and previous study ( Liu et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%